Gradient-coated ternary positive electrode material suitable for wide temperature range and high voltage, preparation method thereof and battery

CN122907615APending Publication Date: 2026-10-13XIAOGAN CORNEX NEW ENERGY INNOVATION TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611061623.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-16
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

常规湿法或固相Al2O3包覆与基体仅为物理附着,缺乏化学键合锚定,这会导致高电压下包覆层快速开裂剥落,释氧抑制较弱致使电解液剧烈氧化

Benefits of technology

(1)本发明所制备的正极材料,其梯度包覆层兼具表面富铝致密区与内部贫铝过渡区,在-30℃低温下界面阻抗≤110Ω,在60℃高温及4.5V高电压下循环200圈容量保持率均不低于89%,且循环后界面阻抗增长缓慢,实现了宽温域、高电压条件下高倍率与高稳定性的同步提升。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The application provides a gradient-coated ternary positive electrode material suitable for a wide temperature range and high voltage, a preparation method thereof and a battery. First, a precursor is subjected to topological chemical denitration treatment by a sodium sulfate solution, unstable nitrate ions between layers are replaced by sulfate ions, a microporous structure is formed in situ, and an activated intermediate phase I is obtained; then, low-temperature pre-anchoring is performed in a lithium-free inert atmosphere, active sulfate on the surface of the intermediate phase I is chemically bonded with nano-aluminum oxide, and a pre-anchored intermediate phase II connected by a covalent bond is generated; finally, a lithium source is added and high-temperature calcination is performed in oxygen, and in the process of diffusion of lithium ions from outside to inside, the aluminum element in the pre-anchored layer forms a gradient LiAlO2 coating layer with gradually reduced aluminum concentration from the surface to the inside, and low interface impedance and high structural stability in a wide temperature range are realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lithium-ion battery cathode materials and their preparation technology, and in particular to a gradient-coated ternary cathode material suitable for a wide temperature range and high voltage, its preparation method, and the battery thereof. Background Technology

[0002] High-nickel ternary cathode materials for lithium secondary batteries (such as LiNi) 0.6 Co 0.2 Mn 0.2 In the process of developing towards higher energy density and adaptability to all climates, O2 faces the following prominent contradictions: (1) The "interface impedance-high temperature protection" are irreconcilable in a wide temperature range scenario: Electric vehicles need to be able to start at -30℃ and withstand long-term cycling at 60℃. Low temperature requires extremely low interface impedance to ensure Li + Rapid migration is a concern; high temperatures also require a highly dense coating to suppress electrolyte corrosion. Currently, conventional uniform Al2O3 coating cannot resolve this contradiction. Increasing the coating amount can improve high-temperature protection, but it leads to a sharp increase in low-temperature impedance. Thinning the coating can alleviate the low-temperature problem, but it will cause the failure rate to accelerate at high temperatures.

[0003] (2) Concurrent occurrence of "lattice oxygen release-coating peeling" under high voltage (≥4.5V): Deep delithiation triggers lattice oxygen release, while the rapid strain along the c-axis causes the coating layer to bear huge stress. Conventional wet or solid Al2O3 coatings are only physically attached to the substrate and lack chemical bonding anchoring, which leads to rapid cracking and peeling of the coating layer under high voltage. The weak oxygen release inhibition causes severe oxidation of the electrolyte.

[0004] (3) Existing technologies cannot solve the above contradictions through simple combinations: electrodeposition to prepare precursors, water washing, wet coating of Al2O3, and high-temperature calcination are known as single steps. However, directly and linearly splicing "electrodeposition → water washing → aluminum source mixing → one-step calcination" can only form a simple physical coating layer, which cannot simultaneously achieve low impedance and high protection over a wide temperature range. Some patents have proposed a "pre-oxidation + one-step calcination" strategy. Pre-oxidation is carried out in an oxygen-containing atmosphere, which can reduce the subsequent lithiation temperature, but it can only achieve densification of the coating layer, and cannot build a chemically bonded anchoring interface, let alone form a compositional gradient transition layer. Therefore, the performance is still not ideal at a high voltage of 4.5V and a low temperature of -30℃. Therefore, there is an urgent need for a manufacturing method that can synergistically combine interlayer stabilization, interface chemical anchoring, and coating layer gradient in situ to fundamentally solve the multi-objective contradictions in wide temperature range and high voltage applications. In this patent, sulfate is used as a bridging medium to construct a pre-anchored interface in a lithium-free inert atmosphere, thereby achieving gradient coating of alumina. Summary of the Invention

[0005] In view of this, the present invention proposes a method for preparing gradient-coated ternary cathode materials suitable for wide temperature range and high voltage. The present invention first performs topological denitration treatment on the precursor using sodium sulfate solution, replacing unstable interlayer nitrate ions with sulfate ions, while simultaneously forming a microporous structure in situ, resulting in an activated mesophase I. Then, low-temperature pre-anchoring is performed under a lithium-free, inert atmosphere, causing the active sulfate ions on the surface of mesophase I to chemically bond with nano-alumina, generating a covalently bonded pre-anchored mesophase II. Finally, a lithium source is added and calcined at high temperature in oxygen. During the diffusion of lithium ions from the outside to the inside, the aluminum elements in the pre-anchored layer form a gradient LiAlO2 coating layer with a gradually decreasing aluminum concentration from the surface to the interior. The cathode material prepared by the above method has a gradient coating layer that combines a dense aluminum-rich region on the surface with an aluminum-poor transition region inside. The interface impedance is ≤110Ω at a low temperature of -30℃, and the capacity retention rate is not less than 89% after 200 cycles at a high temperature of 60℃ and a high voltage of 4.5V. Moreover, the interface impedance increases slowly after cycling, thus achieving a simultaneous improvement in high rate capability and high stability under wide temperature range and high voltage conditions.

[0006] The technical solution of this invention is implemented as follows: In a first aspect, the present invention provides a method for preparing a gradient-coated ternary cathode material suitable for a wide temperature range and high voltage, comprising the following steps: S1, immersing a nitrate precursor in a soluble sulfate solution, dispersing it, and obtaining a first product; S2. The first product is immersed in an Al2O3 dispersion and then subjected to heat treatment to obtain the second product. S3. The second product is mixed with lithium salt and then calcined to obtain a gradient-coated ternary cathode material.

[0007] This invention utilizes SO4 2- Interlayer NO3 replaced by topological chemical intercalation - This process forms a more thermally stable hydroxysulfate mesophase I. The active sulfate ions retained on the surface of mesophase I act as bridging agents, and heat treatment in an inert atmosphere induces the formation of an Al-OS / Al-OM covalently anchored layer (mesophase II), achieving irreversible chemical pinning of Al2O3 nanodots. This method integrates the two independent unit operations of conventional "ion exchange" and "oxide coating" into a continuous synergistic chemical phase transition process, fundamentally different from existing pre-oxidation or simple wet coating schemes.

[0008] This invention utilizes a pre-anchored layer as a diffusion gate for the lithiation reaction during heat treatment in a lithium-free, inert atmosphere, forcing the Al concentration to decrease from the surface inwards during subsequent calcination, thus generating a gradient LiAlO2 solid solution coating layer. This structure simultaneously possesses an aluminum-rich dense region on the surface (high voltage / high temperature protection) and an aluminum-depleted transition region inside (low impedance), providing the structural basis for resolving the contradiction between protection and conduction over a wide temperature range.

[0009] This invention utilizes sodium sulfate topological denitration, where the active sulfate ions retained on the surface of the first product act as a bridging agent. This step simultaneously achieves three functions: eliminating NO3. - / NO2 - The decomposition leads to subsequent structural collapse; the denitrification process forms uniform micropores in situ, which provide channels for low-temperature lithium-ion transport and buffer space for high-voltage oxygen release; reactive sulfate species are retained on the surface of mesophase I as active sites for subsequent Al2O3 chemical bonding anchoring.

[0010] In step S2, under lithium-free and oxygen-free conditions, the active sulfate ions on the surface of mesophase I condense with Al-OH on the Al2O3 surface to form Al-OS bridging bonds; simultaneously, Al-OH condenses with the precursor transition metal hydroxyl groups to form Al-OM (M=Ni, Co, Mn) covalent bonds, and the two together constitute a chemically bonded pre-anchoring layer (mesophase II). This step irreversibly "pins" the Al2O3 nanoparticles to the precursor surface and simultaneously utilizes the micropores left by mesophase I as venting channels to prevent blistering and cracking of the coating layer. This inert atmosphere anchoring mechanism is fundamentally different from conventional oxygen-containing pre-oxidation: the latter aims to oxidize the precursor to lower the lithiation temperature, cannot establish Al-OS bridging, and has no sulfate activation involved.

[0011] In step S3, during the calcination process, Li + Diffusion from the outside in first triggers the Al-OS and Al-OM bonds in the pre-anchored layer to interact with Li. + The reaction generates a solid solution containing LiAlO2. Since the initial spatial position of Al is fixed by the anchoring points, a gradient LiAlO2 coating layer with continuously decreasing Al concentration from the surface to the interior is finally formed: the outermost layer is rich in aluminum and dense, effectively inhibiting high-temperature HF corrosion and high-voltage oxygen release; the inner layer has decreasing aluminum content and transitions continuously with the matrix, maintaining extremely low interfacial resistance.

[0012] Based on the above technical solutions, the soluble sulfate solution further includes any one of sodium sulfate solution, potassium sulfate solution, or ammonium sulfate solution.

[0013] Based on the above technical solution, the mass-to-volume ratio of the nitrate precursor to the sulfate solution is 1:(1~3), and the concentration of the sulfate solution is 1.5 mol / L.

[0014] When the sulfate solution concentration is too low, sulfate replacement is insufficient, and residual nitrate ions can easily cause high-temperature structural collapse and insufficient anchoring sites. When the sulfate solution concentration is too high, sulfate crystals can precipitate on the particle surface, blocking microporous channels and introducing impurity side reactions. A concentration of 1.5 mol / L can achieve complete nitrate replacement, retain a suitable microporous structure, and provide sufficient surface-active sulfate anchoring sites, laying the foundation for Al2O3 covalent bonding and gradient coating.

[0015] Based on the above technical solution, the mass ratio of the first product to the Al2O3 dispersion is 1:(0.5~5)%, and the solid content of the Al2O3 dispersion is 20 wt%.

[0016] If the amount of Al2O3 dispersion is too low, a continuous and dense protective layer cannot be formed, resulting in insufficient ability to suppress oxygen release and resist electrolyte corrosion under high voltage. If the amount of Al2O3 dispersion is too high, excessive insulating aluminum components will accumulate on the surface, significantly increasing low-temperature interfacial impedance and degrading rate performance. Controlling the amount in the range of 0.5 to 5.0 wt% can form a continuous gradient structure with aluminum-rich surface and aluminum-poor interior, balancing the requirements of high-temperature and high-voltage protection with low-temperature and low-impedance conduction.

[0017] Based on the above technical solutions, the particle size of the Al2O3 dispersion is further specified to be between 5 and 20 nm.

[0018] Based on the above technical solution, the heat treatment further includes heat treatment in an inert atmosphere at a temperature of 300~400℃.

[0019] Below 300℃, the activation energy of the reaction is insufficient, making it difficult for active sulfate ions to fully condense with nano-alumina and transition metal hydroxyl groups, thus failing to form stable Al-OS and Al-OM covalent bonds. The reaction is merely physical adsorption, resulting in weak pre-anchoring. Above 400℃, active sulfate ions decompose and are lost due to thermal stress. Simultaneously, the in-situ micropores of the precursor are sintered and closed, and the layered lattice structure is damaged, hindering the formation of the subsequent gradient coating interface. The 300–400℃ temperature range ensures that sulfate ion bridging forms a stable chemically bonded pre-anchored structure while preserving the precursor micropores and layered framework, providing structural support for the subsequent high-temperature calcination to construct a gradient coating layer with a smoothly decreasing aluminum concentration.

[0020] Based on the above technical solution, the lithium salt in step S3 further includes any one of LiOH·H2O, LiCO3 or LiNO3, and the mass ratio of the lithium salt to the second product is 1:(8~12).

[0021] Based on the above technical solution, the calcination further includes: heating to 700-900℃ at a rate of 1-3℃ / min and calcining for 8-12 hours.

[0022] A gradual heating rate of 1–3℃ / min enables stepwise melting of the lithium source and uniform inward diffusion of lithium ions, matching the gradient growth of aluminum elements. Simultaneously, it facilitates stable degassing and crystallization, ensuring the integrity of the microporous structure without cracking. The optimal calcination range of 700–900℃ guarantees the complete development of the matrix's layered lattice and sufficient lithium embedding, while also promoting the formation of a continuous gradient LiAlO2 coating layer with aluminum-rich surfaces and aluminum-poor interiors by pre-anchored aluminum elements. This simultaneously ensures low impedance over a wide temperature range and high voltage long-cycle stability.

[0023] Based on the above technical solution, the dispersion further includes ultrasonic treatment at 50℃~70℃.

[0024] Based on the above technical solution, the preparation method of the nitrate precursor further includes: using modified nickel foam as the working electrode and a nitrate solution of nickel, cobalt and manganese as the electrolyte, the nitrate precursor is prepared by electrodeposition, wherein the molar ratio of nickel, cobalt and manganese is 2:1:1.

[0025] Based on the above technical solution, the preparation method of the modified nickel foam further includes: soaking nickel foam in dilute sulfuric acid to obtain the modified nickel foam, wherein the concentration of the dilute sulfuric acid is 1~3 mol / L.

[0026] Secondly, the present invention also provides a gradient-coated ternary cathode material suitable for wide temperature range and high voltage, prepared by the above-described preparation method.

[0027] Thirdly, the present invention also provides a battery, wherein the positive electrode material of the battery includes the gradient-coated ternary positive electrode material.

[0028] Compared with the prior art, the present invention has the following beneficial effects: (1) The cathode material prepared by the present invention has a gradient coating layer with both an aluminum-rich dense region on the surface and an aluminum-poor transition region inside. The interface impedance is ≤110Ω at a low temperature of -30℃. The capacity retention rate is not less than 89% after 200 cycles at a high temperature of 60℃ and a high voltage of 4.5V. Moreover, the interface impedance increases slowly after cycling, thus achieving a simultaneous improvement in high rate and high stability under wide temperature range and high voltage conditions. Detailed Implementation

[0029] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0030] In the following specific embodiments, the solid content of the nano-Al2O3 dispersion is 20 wt%, and the particle size is 5-20 nm.

[0031] In the following specific implementation methods, unless otherwise specified, all reagents used are conventional reagents that can be obtained commercially.

[0032] Example 1 This embodiment provides a gradient-coated ternary cathode material suitable for a wide temperature range and high voltage, and its preparation method, including the following steps: S1. The nickel foam was successively dissolved in acetone and 1 mol·L⁻¹. -1 Sonicate in hydrochloric acid for 10 min each, then clean with deionized water and ethanol alternately by sonication and vacuum drying.

[0033] The dried nickel foam was treated with 2 mol·L⁻¹ -1 The modified nickel foam was soaked in dilute sulfuric acid for 8 minutes, the surface was etched and sulfur-containing functional groups were introduced to promote uniform nucleation of the precursor, and then vacuum dried to obtain the modified nickel foam.

[0034] S2. Using modified nickel foam as the working electrode and 100 mL of aqueous solution containing 20 mmol Ni(NO3)2·6H2O, 10 mmol Co(NO3)2·6H2O, and 10 mmol Mn(NO3)2·4H2O as the electrolyte, the in-situ layered hydroxynitrate precursor was deposited in three stages at a constant voltage of -1V (vs. Ag / AgCl) for 10 min each time.

[0035] S3. After washing 5g of the layered hydroxynitrate precursor with deionized water, immerse it in 10ml of a solution with a concentration of 1.5mol·L⁻¹. -1 The first product was obtained by ultrasonic treatment at 60℃ and 50kHz for 10 h in Na2SO4 solution.

[0036] S4. Immerse 5g of the first product in a nano-Al2O3 dispersion, controlling the amount of nano-Al2O3 dispersion added to be 2wt% of the mass of the first product, and cure at 80℃ for 2 h. Then, heat-treat at 350℃ for 1 h under a nitrogen atmosphere at a rate of 5℃ / min to obtain the second product.

[0037] S4. The second product is reacted with LiOH·H2O at a ratio of Li / (Ni) 0.6 Co 0.2 Mn 0.2 (OH) x @Al2O3) = 1:10 mass ratio for mixing and grinding (D 50 The ternary cathode material with gradient coating was obtained by calcining it at 800℃ for 10 h in an oxygen atmosphere with a temperature increase of 2℃ / min (≤ 5 μm).

[0038] Example 2 This embodiment provides a gradient-coated ternary cathode material suitable for a wide temperature range and high voltage, and its preparation method, including the following steps: S1. The nickel foam was successively dissolved in acetone and 1 mol·L⁻¹. -1 Sonicate in hydrochloric acid for 10 min each, then clean with deionized water and ethanol alternately by sonication and vacuum drying.

[0039] The dried nickel foam was treated with 2 mol·L⁻¹ -1 The modified nickel foam was soaked in dilute sulfuric acid for 8 minutes, the surface was etched and sulfur-containing functional groups were introduced to promote uniform nucleation of the precursor, and then vacuum dried to obtain the modified nickel foam.

[0040] S2. Using modified nickel foam as the working electrode and 100 mL of aqueous solution containing 20 mmol Ni(NO3)2·6H2O, 10 mmol Co(NO3)2·6H2O, and 10 mmol Mn(NO3)2·4H2O as the electrolyte, the in-situ layered hydroxynitrate precursor was deposited in three stages at a constant voltage of -1V (vs. Ag / AgCl) for 10 min each time.

[0041] S3. After washing 5g of the layered hydroxynitrate precursor with deionized water, immerse it in 5ml of a solution with a concentration of 1.5mol·L⁻¹. -1 The first product was obtained by ultrasonic treatment at 50℃ and 50kHz for 8 h in a Na2SO4 solution.

[0042] S4. Immerse 5g of the first product in a nano-Al2O3 dispersion, controlling the amount of nano-Al2O3 dispersion added to be 0.5wt% of the mass of the first product, and cure at 80℃ for 2 h. Then, heat-treat at 300℃ for 1 h under a nitrogen atmosphere at a rate of 5℃ / min to obtain the second product.

[0043] S4. Mix 5g of the second product with LiOH·H2O at Li / (Ni) 0.6 Co 0.2 Mn 0.2 (OH) x @Al2O3) = 1:12 mass ratio for mixing and grinding (D 50 The material with a thickness of ≤ 5 μm was calcined at 700℃ for 12 h in an oxygen atmosphere by heating at 1℃ / min to obtain a gradient-coated ternary cathode material.

[0044] Example 3 This embodiment provides a gradient-coated ternary cathode material suitable for a wide temperature range and high voltage, and its preparation method, including the following steps: S1. The nickel foam was successively dissolved in acetone and 1 mol·L⁻¹. -1 Sonicate in hydrochloric acid for 10 min each, then clean with deionized water and ethanol alternately by sonication and vacuum drying.

[0045] The dried nickel foam was treated with 2 mol·L⁻¹ -1 The modified nickel foam was soaked in dilute sulfuric acid for 8 minutes, the surface was etched and sulfur-containing functional groups were introduced to promote uniform nucleation of the precursor, and then vacuum dried to obtain the modified nickel foam.

[0046] S2. Using modified nickel foam as the working electrode and 100 mL of aqueous solution containing 20 mmol Ni(NO3)2·6H2O, 10 mmol Co(NO3)2·6H2O, and 10 mmol Mn(NO3)2·4H2O as the electrolyte, the in-situ layered hydroxynitrate precursor was deposited in three stages at a constant voltage of -1V (vs. Ag / AgCl) for 10 min each time.

[0047] S3. After washing 5g of the layered hydroxynitrate precursor with deionized water, immerse it in 15ml of a solution with a concentration of 1.5mol·L⁻¹. -1 The first product was obtained by sonicating in a Na2SO4 solution at 60°C for 10 h, followed by washing and drying.

[0048] S4. Immerse 5g of the first product in a nano-Al2O3 dispersion, controlling the amount of nano-Al2O3 dispersion added to be 5wt% of the mass of the first product, and cure at 80℃ for 2 h. Then, heat-treat at 400℃ for 1 h under a nitrogen atmosphere at a rate of 5℃ / min to obtain the second product.

[0049] S4. Mix 5g of the second product with LiOH·H2O at Li / (Ni) 0.6 Co 0.2 Mn 0.2 (OH) x @Al2O3) = 1:8 mass ratio for mixing and grinding (D 50 The material with a thickness of ≤ 5 μm was calcined at 900℃ for 8 h in an oxygen atmosphere by heating at 3℃ / min to obtain a gradient-coated ternary cathode material.

[0050] Example 4 This embodiment provides a gradient-coated ternary cathode material suitable for wide temperature range and high voltage and its preparation method. The difference from Embodiment 1 is that the amount of nano Al2O3 dispersion added in this embodiment is 1.0 wt% of the mass of the first product.

[0051] Example 5 This embodiment provides a gradient-coated ternary cathode material suitable for wide temperature range and high voltage and its preparation method. The difference from Embodiment 1 is that the amount of nano Al2O3 dispersion added in this embodiment is 1.5 wt% of the mass of the first product.

[0052] Example 6 This embodiment provides a gradient-coated ternary cathode material suitable for wide temperature range and high voltage and its preparation method. The difference from Embodiment 1 is that the amount of nano Al2O3 dispersion added in this embodiment is 2.5 wt% of the mass of the first product.

[0053] Example 7 This embodiment provides a gradient-coated ternary cathode material suitable for a wide temperature range and high voltage, and its preparation method. The difference from Embodiment 1 is that potassium sulfate solution is used instead of sodium sulfate solution, and Li2CO3 is used instead of LiOH·H2O.

[0054] Example 8 This embodiment provides a gradient-coated ternary cathode material suitable for a wide temperature range and high voltage, and its preparation method. The difference from Embodiment 1 is that ammonium sulfate solution is used instead of sodium sulfate solution, and LiNO3 is used instead of LiOH·H2O.

[0055] Comparative Example 1 The difference between this comparative example and Example 1 is that in step S3 of this comparative example, the amount of Na2SO4 solution used is 0. The remaining steps are the same as in Example 1.

[0056] Comparative Example 2 The difference between this comparative example and Example 1 is that in step S3 of this comparative example, the Na2SO4 solution is replaced with a NaNO3 solution of the same concentration. The remaining steps are the same as in Example 1.

[0057] Comparative Example 3 The difference between this comparative example and Example 1 is that the amount of Al2O3 dispersion added is 0.

[0058] Comparative Example 4 The difference between this comparative example and Example 1 is that step S4 does not include heat treatment.

[0059] Step S4: Immerse the first product in an Al2O3 dispersion, controlling the Al2O3 addition amount to be 1.5% of the mass of the first product, and cure at 80°C for 2 hours. The remaining steps are the same as in Example 1.

[0060] Comparative Example 5 The difference between this comparative example and Example 1 is that the layered hydroxynitrate precursor was first immersed in an Al2O3 dispersion, and then immersed in a Na2SO4 solution.

[0061] S3. After washing 5g of the layered hydroxynitrate precursor with deionized water, immerse it in an Al2O3 dispersion, controlling the Al2O3 addition to be 1.5% of the mass of the first product, and cure at 80℃ for 2 h. Then, heat treat it at 350℃ for 1 h under a nitrogen atmosphere with a temperature increase of 5℃ / min to obtain the first product.

[0062] S4. Immerse 5g of the first product in 10ml of a solution with a concentration of 1.5 mol·L⁻¹. -1 The second product was obtained by sonication at 60°C for 10 h in a Na₂SO₄ solution. The remaining steps are the same as in Example 1.

[0063] Comparative Example 6 The difference between this comparative example and Example 1 is that: the layered hydroxynitrate precursor obtained by electrodeposition was washed with water and pre-oxidized directly at 350°C for 1 h in an air atmosphere, and then mixed with 2.0 wt.% Al2O3 and LiOH·H2O, and calcined at 800°C for 10 h in one step, and labeled as NCM@AO-2.0-PO.

[0064] Performance testing 1. TOF-SIMS depth profiling was used to test the Al content of the cathode materials prepared in Example 1 and Comparative Examples 1-6. 3+ The normalized strengths are shown in Table 1.

[0065] Table 1 Performance Comparison Data

[0066] As shown in Table 1, Al in Example 1 3+ The strength decreases smoothly and continuously with depth, indicating that the aluminum content gradually decreases from the surface inwards, forming a gradient transition layer rather than a simple physical adhesion layer. This gradient structure can reduce interfacial stress, lower impedance, and improve structural stability under high voltage.

[0067] In Comparative Example 3, the amount of Al2O3 dispersion added was 0, and the Al content at each depth was... 3+ The strength of all samples was close to that of the bulk material, with no gradient coating. The cathode material was directly exposed to the electrolyte at high temperature / high voltage, and its capacity retention at 60℃ and 4.5V was the worst among all samples. Comparative Examples 1, 2, 4, 5, and 6 (Al) 3+ The strength drops sharply around 150s, indicating that the interface between the aluminum layer and the substrate is abrupt and easily peels off under high voltage. Comparative Examples A, B, and E (other methods): Al 3+The strength drops sharply around 150s (e.g., from 0.95 to 0.08), indicating that there is an abrupt interface between the aluminum layer and the substrate, which is prone to peeling off under high voltage.

[0068] 2. The gradient-coated ternary cathode materials prepared in Examples 1-6 and Comparative Examples 1-6 were assembled into coin cells, and the battery performance was tested. The testing methods included: With an active material / conductive carbon black / PVDF ratio of 90:5:5, coated with aluminum foil, and a compacted density of 3.2 g / cm³. 3 The electrodes were assembled to obtain the battery: CR2032, 1M LiPF6EC / DMC (1:1), Celgard 2400 separator.

[0069] Perform the following routine tests: 2.8–4.3V, 0.1C activation, 1C cycling, 25℃; Wide temperature range: -30℃ EIS, 60℃ 1C cycle; High voltage: 2.8~4.5V, 1C cycle, 25℃.

[0070] The test results are shown in Table 2.

[0071] Table 2 Performance Comparison Data

[0072] As shown in Table 2, Example 1 is optimal in all three indicators: low impedance at -30℃, high retention rate at 60℃, and high retention rate at 4.5V, proving that the gradient coating layer successfully reconciles the contradiction between high-temperature protection and low-temperature conductivity.

[0073] Although Comparative Example 2 can maintain the structural integrity of the precursor (better than Comparative Example 1 in 25℃ cycling), it cannot form Al-OS covalent bonds with Al2O3 due to the lack of active sulfate groups, resulting in a significant decrease in capacity at 60℃ and 4.5V high voltage cycling. This confirms that sulfate bridging is a necessary condition for achieving gradient coating and interface strengthening.

[0074] In Comparative Example 4, the coating peeled off during 4.5V cycling, resulting in a sharp drop in retention. Comparative Example 5 performed worse than Comparative Example 1, confirming that sulfate bridging and the correct sequence of steps are necessary conditions for forming a strong anchor.

[0075] Although Comparative Example 6 performed slightly better than Comparative Example 4, it was far inferior to Example 1, especially in terms of impedance at -30°C and high voltage retention rate, indicating that the sulfate bridging and anchoring mechanism under an inert atmosphere is irreplaceable.

[0076] In summary, this invention first performs topological denitration treatment on the precursor using sodium sulfate solution, replacing unstable nitrate ions with sulfate ions and simultaneously forming a microporous structure in situ, resulting in an activated mesophase I. Then, low-temperature pre-anchoring is performed under a lithium-free, inert atmosphere, causing the active sulfate ions on the surface of mesophase I to chemically bond with nano-alumina, generating a covalently bonded pre-anchored mesophase II. Finally, a lithium source is added and calcined at high temperature in oxygen. During the diffusion of lithium ions from the outside to the inside, the aluminum element in the pre-anchored layer forms a gradient LiAlO2 coating layer with a gradually decreasing aluminum concentration from the surface to the interior. The cathode material prepared by the above method has a gradient coating layer that combines a dense aluminum-rich surface region with an aluminum-poor transition region inside. At -30℃, the interfacial impedance is ≤110Ω, and after 200 cycles at 60℃ and 4.5V, the capacity retention is not less than 89%, with a slow increase in interfacial impedance after cycling. This achieves simultaneous improvement in high rate capability and high stability under wide temperature range and high voltage conditions.

[0077] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A method for preparing gradient-coated ternary cathode materials suitable for wide temperature range and high voltage, characterized in that, The process includes the following steps: S1, immersing the nitrate precursor in a sulfate solution, dispersing it, and obtaining the first product; S2. The first product is immersed in an Al2O3 dispersion and then subjected to heat treatment to obtain the second product. S3. The second product is mixed with lithium salt and then calcined to obtain a gradient-coated ternary cathode material.

2. The preparation method according to claim 1, characterized in that, The sulfate solution includes any one of sodium sulfate solution, potassium sulfate solution, or ammonium sulfate solution.

3. The preparation method according to claim 1, characterized in that, The method for preparing the nitrate precursor includes: using a nickel, cobalt, and manganese nitrate solution as an electrolyte, the nitrate precursor is prepared by electrodeposition.

4. The preparation method according to claim 3, characterized in that, The mass-to-volume ratio of the nitrate precursor to the soluble sulfate solution is 1:(1~3), and the concentration of the sulfate solution is 1.5 mol / L.

5. The preparation method according to claim 1, characterized in that, The mass ratio of the first product to the Al2O3 dispersion is 1:(0.5~5)%, and the solid content of the Al2O3 dispersion is 20 wt%.

6. The preparation method according to claim 1, characterized in that, The heat treatment includes heat treatment in an inert atmosphere at a temperature of 300~400°C.

7. The preparation method according to claim 1, characterized in that, The lithium salt in step S3 includes any one of LiOH·H2O, Li2CO3 or LiNO3, and the mass ratio of the lithium salt to the second product is 1:(8~12).

8. The preparation method according to claim 1, characterized in that, The calcination includes heating to 700-900℃ at a rate of 1-3℃ / min and calcining for 8-12 hours.

9. A gradient-coated ternary cathode material suitable for wide temperature range and high voltage, prepared by any one of the preparation methods described in claims 1 to 8.

10. A battery, characterized in that, The positive electrode material of the battery includes the gradient-coated ternary positive electrode material as described in claim 9.